Kinetics and Mechanism of Oxidation of Substituted Benzaldehydes by Peroxydisulphate - Hiran, B.L.; Jain, S.L.; Joshi, S.N. (Asian Journal of Chemistry, 2010)
Kinetics of the oxidation of substituted benzaldehydes by peroxydisulphate have been studied. The reaction has a first order dependence on (S2O2–8) concentration. The rate is independent of the Ag(I) concentration. The rate of oxidation of substrate is dependent on the concentration of substrate. Michaelis Menten type of rate dependence on the substrate has been observed. A tentative mechanism has been proposed based on experimental data.